Automated composite layup & spray up - Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2005)
The automated composite layup and spray up program focuses on the various automated processes and equipment developed to manufacture composite products of high quality. The use of CNC gantry ply-cutters, robots, tape lamination machines and fiber placement machines are among the automated technologies detailed
Title from title screen
DVD format
Keywords: Reinforced plastics; Composite materials; Composite construction